2007
DOI: 10.1080/10611860601143727
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation and pharmacokinetics in dogs of guar gum and Eudragit FS30D-coated colon-targeted pellets of indomethacin

Abstract: A pH- and enzyme-dependent colon-targeted multi-unit delivery system of indomethacin was developed by coating guar gum and Eudragit FS30D sequentially onto drug-loaded pellets in a fluidized bed coater. In vitro studies showed that smaller coating weight gain of guar gum resulted in reduced release lag time t10 (10% release time), but favored degradation by enzymes (galactomannanase). A cumulative weight gain (CWG) of 44% provided sufficient enzymatic sensitivity and protection of the core. Under gradient pH c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The supernatant was analyzed by HPLC for indomethacin content. This method has been validated for linearity, accuracy, precision, extraction recovery and limit of quantification (Ji et al, 2007).…”
Section: Determination Of Indomethacin In Tablets Release Media and mentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was analyzed by HPLC for indomethacin content. This method has been validated for linearity, accuracy, precision, extraction recovery and limit of quantification (Ji et al, 2007).…”
Section: Determination Of Indomethacin In Tablets Release Media and mentioning
confidence: 99%
“…The detection wavelength was set at 320 nm. The above HPLC method was also adapted for the determination of indomethacin in dog plasma (Ji et al, 2007). Samples were prepared by liquid-liquid extraction.…”
Section: Determination Of Indomethacin In Tablets Release Media and mentioning
confidence: 99%
“…Fluidized bed coating is mainly used to develop modified release (13), pulsatile release (14) or to increase drug bioavailability (15). There are only a few studies reported where fluidized bed coating was implemented for tastemasking purposes (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used dissolution testing methods for these delivery systems (which have few limitations 11 ) involve the addition of enzymes, [11][12][13][14][15][16][17] rat cecal contents, [18][19][20][21] and human fecal slurries. [22][23][24][25][26][27][28][29][30][31] Under colonic conditions, enzymes are continuously replenished by the microbiota that secretes these enzymes.…”
Section: Introductionmentioning
confidence: 99%